2014
DOI: 10.2337/db13-1817
|View full text |Cite
|
Sign up to set email alerts
|

IKKε Is Key to Induction of Insulin Resistance in the Hypothalamus, and Its Inhibition Reverses Obesity

Abstract: IKK epsilon (IKK«) is induced by the activation of nuclear factor-kB (NF-kB). Whole-body IKK« knockout mice on a high-fat diet (HFD) were protected from insulin resistance and showed altered energy balance. We demonstrate that IKK« is expressed in neurons and is upregulated in the hypothalamus of obese mice, contributing to insulin and leptin resistance. Blocking IKK« in the hypothalamus of obese mice with CAYMAN10576 or small interfering RNA decreased NF-kB activation in this tissue, relieving the inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 38 publications
0
45
0
1
Order By: Relevance
“…Previous studies have implicated IKKε in the pathology of a wide array of diseases, including cancer, inflammatory, and metabolic diseases [4,8,18]. Many studies indicate a critical role of IKKε in the pathophysiology of inflammatory diseases; it has been reported that inflammation appeared to be reduced in IKKε KO mice [19,21], and our previous study indicated that deficiency of IKKε inhibits inflammation and induces cardiac protection [7].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Previous studies have implicated IKKε in the pathology of a wide array of diseases, including cancer, inflammatory, and metabolic diseases [4,8,18]. Many studies indicate a critical role of IKKε in the pathophysiology of inflammatory diseases; it has been reported that inflammation appeared to be reduced in IKKε KO mice [19,21], and our previous study indicated that deficiency of IKKε inhibits inflammation and induces cardiac protection [7].…”
Section: Discussionmentioning
confidence: 77%
“…Pathways. This study is an effort to glean mechanistic insights into the underlying cause of AAA pathology, considering the involvement of ERK1/2 signaling in AAA [12] and the published studies demonstrating that IKKε is required for the induction of proinflammatory cytokines [18] and ERK1/2 activation [19]. We further hypothesized that IKKε might participate in the development of AAA via activation of the ERK1/2 pathways.…”
Section: Ikkε Regulated Ang Ii-activated Erk1/2 Signalingmentioning
confidence: 99%
“…Our data correlate with a recent study showing that intrahypothalamic inhibition of IKKɛ decreases TNF-alpha levels, improves insulin and leptin sensitivity, and decreases food intake. 98 The molecular binomial TBK1/IKKɛ seems to have more versatile functions related to the regulation of body glucose homeostasis. In a recent study, it was shown that inhibition of TBK1/IKKɛ in obese mice induces the release of IL-6, which stimulates phosphorylation of the Stat3 pathway in the liver, suppressing gluconeogenesis.…”
Section: The Tlr-ikkβ-nf-κb Pathway In the Development Of Type 2 Diabmentioning
confidence: 99%
“…IKKε knockout (KO) mice are protected from the diet induced obesity and insulin resistance. Inhibition of IKKε with either chemical means on small interfering RNA suggested a reduction in the inhibitory phosphorylation of IRS1Ser 307 and insulin resistance via IR/IRS-1/Akt and JAK2/STAT3 pathways [80]. …”
Section: Iκb Kinase (Ikk)mentioning
confidence: 99%